1983
DOI: 10.1107/s0021889883010158
|View full text |Cite
|
Sign up to set email alerts
|

G-TDSCOR: one-phonon TDS corrections for measured integrated Bragg intensities

Abstract: (2) As compared with Frevel's method, the least-squares method proposed in the present work for intensity matching can give better results and provide more information which may be helpful for further discrimination of the candidates.References DISMORE, P. F. (1976). Adv. X-ray Anal. 20, 113-123. FREVEL, U K. (1965). Anal. Chem. 37, 471-482. FREVEL, U K. (1966). Anal. Chem. 38, 1914-1920. FREVEL, U K. (1976. Adv. X-ray Anal. 20, 15-25. FREVEL, L. K. & ADAMS, C. E. (1968). Anal. Chem. 40, 133540, -134040… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…(1) 2.748 (7) x 10 Scale (2) 2.747 (6) × 10 r* 2.7 (3) x 10 3 I/3~_q 0.81 (5) values are all larger than those in Table 3, especially B33(Se) [B~(Cd)=I.71, B33(Cd)=2-23, B,~(Se)= 2.00 and B33(Se)=3.38 A2]. Sakata, Stevenson & Harada (1983) showed that using the TDS corrections of Harada & Sakata (1974) and Sakata & Harada (1976), based on the spherical-volume approximation (SVA), did not significantly affect the value of/3cose (see SMB). The value of /~CdSe is 1"474 (4)A 2, cf.…”
Section: Resultsmentioning
confidence: 86%
“…(1) 2.748 (7) x 10 Scale (2) 2.747 (6) × 10 r* 2.7 (3) x 10 3 I/3~_q 0.81 (5) values are all larger than those in Table 3, especially B33(Se) [B~(Cd)=I.71, B33(Cd)=2-23, B,~(Se)= 2.00 and B33(Se)=3.38 A2]. Sakata, Stevenson & Harada (1983) showed that using the TDS corrections of Harada & Sakata (1974) and Sakata & Harada (1976), based on the spherical-volume approximation (SVA), did not significantly affect the value of/3cose (see SMB). The value of /~CdSe is 1"474 (4)A 2, cf.…”
Section: Resultsmentioning
confidence: 86%
“…The data (70 independent reflections) were corrected for the contributions from anisotropic first-order thermal diffuse scattering (TDS) by acoustic lattice vibrations. The program used is that described by Sakata, Stevenson & Harada (1983). The elastic constants used were those of McSkimin & Thomas (1962) and Cottam & Saunders (1975) for CdTe and HgTe, respectively, and an average of the two sets was taken (the differences being only 0.2, 0.6 and 6.3% for C~1, C12 and C44, respectively).…”
Section: Results -Iimentioning
confidence: 99%
“…As an example, the values of ((A-~)tm) were evaluated by numerical integration using the TDS correction program of Sakata, Stevenson & Harada (1983) for CdS. The elastic constants used were those of Berlincourt, Jaffe & Shiozawa (1963).…”
Section: Comparison Of Experiments and Theorymentioning
confidence: 99%